Temporal evolution of under-ice meltwater layers and false bottoms and their impact on summer Arctic sea ice mass balance - Salganik, Evgenii; Katlein, Christian; Lange, Benjamin; Matero, Ilkka; Lei, Ruibo; Fong, Allison A.; Fons, Steven; Divine, Dmitry; Oggier, Marc; Castellani, Giulia; Bozzato, Deborah; Chamberlain, Emelia; et al. (Elementa: Science of the Anthropocene, 2023)
Low-salinity meltwater from Arctic sea ice and its snow cover accumulates and creates under-ice meltwater layers below sea ice.These meltwater layers can result in the formation of new ice layers, or false bottoms, at the interface of this low-salinity meltwater and colder seawater. As part of the Multidisciplinary drifting Observatory for the Study of the Arctic Climate (MOSAiC), we used a combination of sea ice coring, temperature profiles from thermistor strings and underwater multibeam sonar surveys with a remotely operated vehicle (ROV) to study the areal coverage and temporal evolution of under-ice meltwater layers and false bottoms during the summer melt season from mid-June until late July. ROV surveys indicated that the areal coverage of false bottoms for a part of the MOSAiC Central Observatory (350 by 200 m2 ) was 21%. Presence of false bottoms reduced bottom ice melt by 7–8% due to the local decrease in the ocean heat flux, which can be described by a thermodynamic model. Under-ice meltwater layer thickness was larger below first-year ice and thinner below thicker second-year ice. We also found that thick ice and ridge keels confined the areas in which under-ice meltwater accumulated, preventing its mixing with underlying seawater. While a thermodynamic model could reproduce false bottom growth and melt, it could not describe the observed bottom melt rates of the ice above false bottoms. We also show that the evolution of under-ice meltwaterlayer salinity below first-year ice is linked to brine flushing from the above sea ice and accumulating in the meltwater layer above the false bottom.The results of this study aid in estimating the contribution of underice meltwater layers and false bottoms to the mass balance and salt budget for Arctic summer sea ice.